PENGARUH MODEL PEMBELAJARAN (CC) BERBASIS SCAFFOLDING TERHADAP KEMAMPUAN SCIENTIFIC REASONING FISIKA SISWA SMA - Devi Tri Ulul Azmi; Sri Astutik; Subiki Subiki (Universitas Negeri Surabaya, 2021)
The purpose of the research is conducted to examine the effect of Scaffolding-based (CC) learning models on the ability of scientific reasoning physics of high school students. The research population was MAN Bondowoso 2019/2020 students and the research sample was the students of class XI IPA 1 and XI IPA 2. The research techniques used were observation, tests and documentation. There are two stages of data analysis technique, they are normality test and independent sample t-test using SPSS version 23. The result shows that the experimental class and control class data are normally distributed, that is the sig value. > 0.05. Independent test sample t-test using SPSS 23 on the scientific reasoningphysics capability obtained sig. (2-tailed) by 0,038 and the result of sig. (1-tailed) for 0,019 meaning that the test is <0.05. The results showed that the model based on Scaffolding had a significant effect on the ability of scientific reasoning physics of high school students of high school students.